Computational analysis to define efficacy & molecular mechanisms of 7, 4’- Dihydroxyflavone on eosinophilic esophagitis: Ex-vivo validation in human esophagus biopsies - Maskey, Anish R.; Wang, Zhen-Zhen; Chen, Xin; Dunkin, David; Yang, Nan; Soffer, Gary; Yuan, Qian; Li, Xiu-Min (Frontiers in Immunology, 2022)
Eosinophilic Esophagitis (EoE) is a chronic condition characterized by eosinophilic inflammation of the esophagus which leads to esophageal dysfunction with common symptoms including vomiting, feeding difficulty, dysphagia, abdominal pain. Current main treatment options of EoE include dupilumab, dietary elimination and swallowed steroids. Dupilumab is indicated only for treatment of patient aged 12 years and older. Diet elimination approach could lead to identifying the trigger food(s), but it often requires repeated upper endoscopy with general anesthesia and potentially could negatively affect nutrition intake and growth of the child and individuals’ quality of life. Although the swallowed steroid treatment of effective, the EoE will universally recur after discontinuation of the treatment. Digestive Tea formula (DTF) has been used by the Traditional Chinese Medicine (TCM) practice to improve GI symptoms in EoE patients, including abdominal pain, reflux, and abnormal bowel movement. Previously, a flavonoid small molecule compound 7, 4 dihydroxy flavone (DHF) from Glycyrrhiza uralensis in DTF inhibited eotaxin, Th2 cytokine and IgE production in vitro and in vivo. The objective of this study is to investigate the mechanisms underlying DHF improvement of symptoms related to EoE using computational modeling followed by ex vivo validation using cultured human esophagus biopsy specimen from patients with EoE with or without DHF. Computational analyses defined 29 common targets of DHF on EoE, among which TNF-α, IL-6, IL1β, MAPK1, MAPK3 and AKT1 were most important. Docking analysis revealed that DHF directly binds TNF-α with a free binding energies of -7.7 kcal/mol. Subsequently, in the human esophagus biopsy culture system, significant reduction in levels of TNF-α, IL-6, IL-8 and IL1-β was found in the supernatant of biopsy sample cultured with DHF. Furthermore, the gene expression profile showed significant reduction in levels of TNF- α, IL1-β, IL-6, CCND and MAPK1 in the esophagus biopsy sample cultured with DHF. Taken together, the current study provides us an insight into the molecular mechanisms underlying multi-targeted benefits of DHF in the treatment of EoE and paves the way for facilitating more effective EoE therapies.